The necessity for enhancing awareness of tuberculosis starting from the early college semesters: empirical evidence from a cross-sectional research - Chen, Xinyi; Peng, Ying; Zhou, Lin; Wang, Fei; Chen, Bin; Qu, Yan (Frontiers in Public Health, 2023)
Background College students, especially those in the lower grades, constitute the main high-risk population for tuberculosis (TB). Insufficient knowledge about TB among college students contributes to an increased risk of TB infection. In Zhejiang Province, China, limited research has been conducted recently on the awareness of TB in schools among college students. Therefore, this study aims to gain insight into TB knowledge among low-grade college students in Zhejiang Province and develop effective strategies for TB education targeted at this specific population. Methods A cross-sectional survey was conducted between 1st and 20th May 2022 in 20 colleges in Zhejiang Province, southeastern China. The survey aimed to assess the level of TB awareness among 1st and 2nd-year college students. Chi-square tests were performed to compare the rates, while multivariate logistic regression was used to identify the factors influencing the overall awareness level of students' regarding key knowledge about TB. Results A total of 4,414 lower-grade students participated in the study. The total awareness rate and entire awareness rate of key TB knowledge were 81.6 and 25.3%, respectively. Participants who demonstrated a relatively poor understanding of the definition were (51.0%), curable outcomes (75.7%), and preventive measures of TB (76.1%). Female participants [adjusted odds ratio (aOR):1.44; 95% confidence interval (CI):1.25–1.65], medical students (aOR:2.00; 95%CI:1.63–2.64), had a high level of monthly expenditures (aOR:2.50; 95%CI:1.49–4.19), had prior TB health education (aOR:1.95; 95%CI:1.68–2.25) and previous exposure to TB patients (aOR:2.13; 95% CI:1.48–3.08) indicating a better level of awareness of key knowledge about TB. Among the students, 58.5% expressed their willingness to acquire TB knowledge through “broadcasting, television, films, and audiovisual materials.” Conclusions The total awareness rate of key knowledge among low-grade college students in Zhejiang did not meet the national requirements. To effectively prevent TB in schools, it is crucial to develop a comprehensive understanding of the disease among college students. Therefore, it is necessary to enhance TB awareness through theoretical and practical education, starting from the early semesters of college.